Spin Glass Transition of Magnetic Ionic Liquids Induced by Self-Assembly - Yang, Jie (Langmuir : the ACS journal of surfaces and colloids, 2025)
Spin glass (SG), in which the spins are glassy, has attracted broad attention for theoretical study and prospective application. SG states are generally related to disordered or frustrated spin systems, which are usually observed in inorganic magnets. Herein, supramolecular magnetic ionic liquid (TMTBDI[FeCl4]) self-assemblies are prepared by solution self-assembly via hydrophobic and π-π stacking interactions. The supramolecular self-assemblies are in short-range lattice ordering and long-range disordering structures, as the lattice self-assemblies with the tens of nanometer scale are distributed randomly to form a long-range disorder. The shortest Fe(III)-Fe(III) distance is calculated to be ca. 2.4 Å from transmission electron microscopy (TEM) results. The magnetic properties of the supramolecular self-assemblies are studied via direct current (DC) and alternating current (AC) magnetic susceptibility characterizations. It is noted that TMTBDI[FeCl4] is paramagnetic before self-assembly. However, the supramolecular self-assemblies exhibit a strong ferromagnetic interaction due to the short Fe(III)-Fe(III) distance. The AC results show that the supramolecular self-assemblies are in the SG state at low temperatures as the imaginary part of the susceptibility moves to high temperatures with frequency. The self-assembly-induced spin glass transition of TMTBDI[FeCl4] is due to the long-range disordering and short-range ordering structures of the self-assemblies, which induces a frustrated spin system